Pupils as participants in prevention of bullying in schools - Marković Marija (Specijalna Edukacija i Rehabilitacija, 2014)
Students play an important role in creating a school climate that does not support bullying, given the fact that students are more often than teachers present when it happens and aware of the frequency of bullying. It has been shown that inclusion of students in the programs of bullying prevention contributes to the positive results of their application. It is very important that students become aware of their role in situations of bullying and that they develop appropriate social skills that will enable them to react appropriately. The paper aims to highlight the importance of engaging students in the framework of intervention and prevention programs implemented in the school context. We emphasize the ways in which students can be involved in the prevention of violence and present some of the violence prevention programs in which students played a key role.